Percutaneous tricuspid valve replacement in childhood - Emmel, Mathias (Ann Pediatr Cardiol, 2015)
Percutaneous replacement of the tricuspid valve with a bovine jugular venous valve (melody valve) was successfully undertaken in a 9-year-old boy. The patient had a previous history of bacterial endocarditis of the native tricuspid valve in infancy. Initially, a pericardial patch valve was created, followed by surgical replacement of the valve using a biological tissue valve at 4 years of age. Progressive stenosis and regurgitation of the biological valve, with severe venous congestion and resulting hepatic dysfunction prompted percutaneous valve replacement.